The Influence of Academic Service Quality, Campus Facilities, and University Image on Student Satisfaction Faculty Of Economics and Business Universitas Swadaya Gunung Jati Cirebon - Maulana, Adrian; Pratminingsih, Sri Astuti; Suhardi, Dadang (Universitas Kuningan, 2025)
This study aims to analyze the impact of academic service quality, campus facilities, and university image on student satisfaction at the Faculty of Economics and Business, Universitas Swadaya Gunung Jati Cirebon. The population consists of all active students enrolled in the Faculty of Economics and Business, totaling 4,166 students. The sampling method used is non-probability sampling with a convenience sampling technique, resulting in a sample of 390 students.Descriptive analysis shows that the quality of academic services at FEB UGJ is categorized as good, with an average score of 3.62, although there are several aspects that need improvement, such as the consistency of leadership policies. The assessment of campus facilities is also good, with an average of 3.78; however, the availability of computer facilities is still inadequate. The university's image received positive ratings in brand and social aspects, but its academic image needs enhancement. The average satisfaction score of students indicates a good result, but there is a need to increase student participation in extracurricular activities.Verificative analysis using multiple linear regression indicates that academic service quality, campus facilities, and university image have a significant influence on student satisfaction. The obtained regression model is Y = 0.250 + 0.603X1 + 0.270X2 + 0.442X3, where X1, X2, and X3 represent academic service quality, campus facilities, and university image, respectively. The t-test shows that all independent variables positively contribute significantly to the dependent variable.